SERVICE QUALITY CONTROL MEASUREMENT: QUALITOMETRO II METHOD - Rosna Laksimon; Henry Pribadi (Institute of Research and Community Outreach - Petra Christian University, 2007)
High quality of service is imperative for competitiveness of a service industry. In order to provide much better service, a deeper research on quality service is a necessity. One interesting and challenging aspect in researchin service quality is about measuring service quality. While some methods is proposed for measuring service quality, but every one of them did not offer satisfactory explanation in complex problems of measuring service quality, which is the vagueness and incompleteness in transforming linguistic explanation and scale of one's opinion into numerical scale. One interesting method that incorporate the complexity and vagueness of linguistic explanation and scale into consideration is Qualitometro II method. This method will handle information expressed on linguistic scales without any artificial numeric scalarization and measure and control the quality of service. An interesting study of implementation of Qualitometro II in general medical clinic is conducted to examine the operation and impact of the Qualitometro II method with the assistance of a qualitometro software to ease the complex calculation algorithm. Result of the implementation is presented and evaluated for further study.